Rare Diseases and Syndromes Observed in Newborn Babies with Idiopathic Hypertrophic Pyloric Stenosis - Kaya, Başak; Akduman, Hasan; Dilli, Dilek; Geyik, Cem; Karaman, Ayşe; Uçan, Berna; Kaya, Özkan; Aydoğan, Seda; Zenciroğlu, Ayşegül (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Aim  Although infantile hypertrophic pyloric stenosis is a multifactorial disease caused by genetic and environmental factors, the role of genetic factors has become more important recently. With this study, we aimed to present rare diseases accompanying infantile hypertrophic pyloric stenosis caused by genetic factors.Patients and Methods  This is a retrospective study. Babies who were operated on with the diagnosis of infantile hypertrophic pyloric stenosis in the neonatal intensive care unit between 2000 and 2022 and had additional diseases were included in the study.Results  9.8% of patients diagnosed with infantile hypertrophic pyloric stenosis had an accompanying rare disease.Conclusion  Early diagnosis and treatment of rare diseases associated with infantile hypertrophic pyloric stenosis are of great importance in reducing morbidity/mortality due to these diseases.
Keywords: pyloric stenosis; syndromic; diseases; metabolic; congenital anomaly; concomitant